Intersectionality and Gender-Based Violence: An Empirical Multi-Level Examination of Prevalence and Frequency in Universities and Research Organizations - Humbert, Anne Laure (Violence against women, 2025)
This article provides a multilevel intersectional analysis of the prevalence and frequency of gender-based violence within universities and other research organizations in Europe. Results show not only the high prevalence of gender-based violence in this context, but also that in contrast to the prevailing discourse, that gender-based violence is not solely a “women's problem”, but also a structural issue impacting diverse identities. Data on frequency show that physical and sexual violence usually occurs as isolated incidents, whereas psychological violence and harassment are often repeated.